2019
DOI: 10.1016/j.yebeh.2018.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and needs of parents of young children with active epilepsy: A population-based study

Abstract: To gain a comprehensive understanding of the experiences and needs of parents of young children with epilepsy from a total population sample. The parents (mothers (n=38), fathers (n=9)) of 40/53 (75% of total population) young children ((1-7 years; 23male, 17 female) with 'active' epilepsy (had a seizure in the last year or taking AEDs) were interviewed either in person or over the telephone using a semi-structured interview schedule. The families were resident in the south of the UK. The interviews were audio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…If possible, this should be avoided, as this can lead to a loss of information 11 . Other study results also indicated that parents did not feel sufficiently well informed to talk to their child about epilepsy and did not know how to proceed 8,14–16 . When the children in our study talked about the moment they learnt about their diagnosis, it was clear that many of them had little or no knowledge about epilepsy.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…If possible, this should be avoided, as this can lead to a loss of information 11 . Other study results also indicated that parents did not feel sufficiently well informed to talk to their child about epilepsy and did not know how to proceed 8,14–16 . When the children in our study talked about the moment they learnt about their diagnosis, it was clear that many of them had little or no knowledge about epilepsy.…”
Section: Discussionmentioning
confidence: 67%
“…11 Other study results also indicated that parents did not feel sufficiently well informed to talk to their child about epilepsy and did not know how to proceed. 8,[14][15][16] When the children in our study talked about the moment they learnt about their diagnosis, it was clear that many of them had little or no knowledge about epilepsy. Therefore, they felt that a physician should provide the patients with detailed information about the condition during the first conversation about epilepsy.…”
Section: Discussionmentioning
confidence: 93%
“…Previous research has highlighted the need for high-quality online resources for parents of CWE due to the widespread reported use of the internet to access information and support (Jones et al, 2019). Whilst there are many general online sources of information about sleep available for parents, the large quantity of information can feel overwhelming for parents (Walsh et al, 2015;Cook et al, 2021) and decisions about whether or not to engage with resources can be even more difficult for families where children have particular needs or medical conditions as the advice offered may not obviously appear to be relevant or appropriate for their family circumstances (Zeng and Cheatham, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…An online BSI was chosen for evaluation in this trial due to the RCT evidence of the efficacy of such an approach for similar childhood (Mindell et al, 2006) and adult (Espie et al, 2012) sleep problems in diverse populations. In addition, parents of CWE frequently use the internet to try to access information and support, and others have noted the need for the development of high-quality online resources for parents (Jones et al, 2019). Importantly, an online BSI (i) offers cost effectiveness, (ii) addresses many logistical considerations of rolling out and delivering nationwide interventions, (iii) aligns with future NHS trends in telemedicine, minimising NHS staff burden and the need for staff training to deliver the intervention, and (iv) has the potential to ultimately maximise patient access to the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The basic concepts of simple science can be done by children in learning activities individually or in groups (25)(26)(27) in the classroom under the guidance of teachers or independently through demonstration activities (28) and other evidentiary activities. Children's knowledge needs to be owned early on (29)(30)(31). To record all events experienced through the process of education and learning that is good and right.…”
Section: Literature Reviewmentioning
confidence: 99%